Use of Investigator 24plex GO! To analyse allele frequencies of 21 autosomal STRs in the population of Veracruz state, Mexico - Guadalupe Melo; Keren Uscanga; Mauro López-Armenta; David Avilés-Villada; Pablo Hernández-Romano; Héctor Rangel-Villalobos; P. Aquino; A. Meza; Carlos Jiménez; Patricia Denis; Nayali López-Balderas (Taylor & Francis Group, 2022)
Background Mexican population databases for autosomal STRs are scarce, and no previous studies have been performed with the Qiagen Investigator 24plex GO! Aim To analyse the frequency of 21 autosomal short tandem repeat (STR) loci and forensic parameters in individuals from Veracruz state, Mexico. Subjects and methods A total of 234 unrelated individuals were analysed with the Investigator 24plex GO! Kit, which includes the following autosomal STRs: TH01, D3S1358, vWA, D21S11, TPOX, D1S1656, D12S391, SE33, D10S1248, D22S1045, D19S433, D8S133879, D2S1338, D2S441, D18S51, FGA, D16S539, CSF1PO, D13S317, D5S818, and D7S820. Allele frequencies, forensic parameters, and relationships with neighbouring Mexican populations were estimated. Results The STRs analysed were in Hardy-Weinberg Equilibrium (HWE). The combined matching probability and combined PE were 1.5266 E-24 and 0.999999988711, respectively. The D18S51 and SE33 loci presented the highest Ho (0.8974 and 0.8932) and PE (0.7902 and 0.7815), respectively. The highest PIC (0.9337) and PD (0.9894) values corresponded to SE33. Conversely, D22S1045 had the lowest PIC and PE (0.5533 and 0.3546, respectively). A population cluster among southern Mexican populations, which included non-differentiation between Guerrero and Veracruz states was detected. Conclusion The forensic efficacy of the 21 STRs analysed by the Investigator 24plex GO! Kit was evaluated in the Veracruz state. Moreover, new population clusters that have not yet been described and are related to geographic regions were identified, and these are in agreement with previously reported ancestral differences.